Twenty years of diplomatic relations between Vatican City state and Israel - Secler, Bartłomiej (My University, 2016)
Basic Agreement concluded between the Vatican City State and Israel in 1993 was an important step for the establishment of diplomatic relations . The conclusion of this Agreement is not a question of interreligious and diplomatic, which was associated with the efforts of the Vatican normalization of political relations with various countries . The author has analyzed the document and assess the re- lations in the perspective of twenty years . He also pointed to the fundamental problems in bilateral relations, and presented an assessment of contemporary relationships . The challenge for the future relations both states will be a consequence of the recognition in 2015 by the Vatican City State in- dependence of Palestine .
Keywords: Israel; Vatican City State; Basic Agreement